2014
DOI: 10.1371/journal.pone.0088630
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Retroviral Therapy Is Associated with Decreased Alveolar Glutathione Levels Even in Healthy HIV-Infected Individuals

Abstract: ObjectiveLung infections are a leading cause of death in HIV-infected individuals. Measuring redox in HIV-infected individuals may identify those with chronic oxidative stress who are at increased risk for lung infection. We sought to estimate the association between HIV infection and oxidative stress in the lung, as reflected by decreased levels of glutathione and cysteine in the epithelial lining fluid.MethodsBronchoalveolar lavage (BAL) fluid was collected from healthy HIV-infected subjects and controls. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
1
26
1
Order By: Relevance
“…Impaired AM function is likely responsible for the increased risk of infection seen in these patients. We recently reported [16,19] a significant decrease in glutathione level in bronchoalveolar lavage fluid, as well as attenuated phagocytosis in AMs derived from HIV-1 transgenic rats, which has been shown in the individuals with HIV/AIDS [6,[22][23][24]. In present study, we investigated Nrf2, a master transcription factor that has a critical role in maintenance of redox homeostasis, to understand the mechanisms of the impairment in AMs.…”
Section: Discussionmentioning
confidence: 69%
“…Impaired AM function is likely responsible for the increased risk of infection seen in these patients. We recently reported [16,19] a significant decrease in glutathione level in bronchoalveolar lavage fluid, as well as attenuated phagocytosis in AMs derived from HIV-1 transgenic rats, which has been shown in the individuals with HIV/AIDS [6,[22][23][24]. In present study, we investigated Nrf2, a master transcription factor that has a critical role in maintenance of redox homeostasis, to understand the mechanisms of the impairment in AMs.…”
Section: Discussionmentioning
confidence: 69%
“…Evidence from our group and others suggests that the alveolar space is significantly more oxidized in HIV infection (43). We have shown that the expression and function nuclear factor (erythroid-derived 2)-like 2, the master transcription factor that regulates antioxidant defenses, is compromised in the lung of HIV transgenic rats (44), likely due to the effects of viral proteins in the alveolar space.…”
Section: Alveolar Epitheliummentioning
confidence: 62%
“…However, other studies report that HIV impairs TLR-mediated TNF-a production in the alveolar compartment, decreases in TLR-1 and TLR-4, leading to deficiencies in innate immune response in the presence of ART (124). In addition, measurements of glutathione and cysteine levels in BAL as surrogate markers of oxidative stress in the lung showed no significant differences between HIV-infected and uninfected subjects and that HIV-infected patients without ART had significantly decreased alveolar glutathione levels, suggesting increased oxidative stress in that population (33).…”
Section: Success and Challenges Of Antiretroviralsmentioning
confidence: 96%
“…Further studies by Fan et al pointed to inhibition of the nuclear factor (erythroidderived 2)-like 2/antioxidant response element (Nrf2/ARE) pathway as mechanistic insights into HIV-mediated barrier functions and oxidative status (51). HIV-associated COPD also features low levels of glutathione in the lungs and in the peripheral blood (33). Together, this suggests that the presence of infectious pathogens such as HIV, coupled with abnormal inflammatory responses and oxidative stress, all contribute mechanistically to HIV-COPD.…”
Section: Hiv-associated Challenges In the Lungmentioning
confidence: 99%